A Positioning Method of Temperature Sensors for Monitoring Dam Global Thermal Field - Peng, Haoyang; Lin, Peng; Xiang, Yunfei; Chen, WenQi; Zhou, Shaowu; Yang, Ning; Qiao, Yu (Frontiers in Materials, 2020)
During the concrete pouring process of a dam construction, timely and accurate temperature monitoring is of great significance to reveal the thermal distribution characteristics and evolution process, and control concrete cracking. In this study, a positioning method of temperature sensors (PMTS) in a concrete dam is developed to determine the arrangement of temperature sensors quantitatively. The proposed positioning method is related to the restructured thermal field based on the natural neighbor interpolation algorithm, and the cross-validation. Based on the method, thermometers, distributed optical fibers and infrared thermal imagers are optimally installed in a super-high arch dam for real-time measurement of concrete temperature. The results show that the PMTS is reasonable and reliable for obtaining the dam global thermal field. The on-site temperature monitoring data indicate that the time and space temperature distribution law of the restructured thermal field is consistent with the actual situation of the super-high arch dam. In addition, the cons and pros, and improvement of the PMTS are further discussed. The proposed PMTS is a valuable method to monitor the global thermal field of concrete dams.